The Effect of Remediation of Crude Oil Contaminated Land on Agricultural Resources in Umuechem in Etche Local Government Area of Rivers State, Nigeria - Elendu, Chukwuemeka J.; Wokekoro, Ebiwari; Akujuru, Victor A. (Environmental Management and Sustainable Development, 2022)
Contamination is the release of hazardous materials into the environment; which could be in the form of: waste, petroleum hydrocarbons and other unwanted materials. The release of these hazardous materials could affect soil nutrients and aggravate biodiversity loss. When the soil nutrient is impacted, it negatively affects its crop yield and production capabilities. Once there is contamination of the environment, remediation becomes necessary. This paper examines the effects of remediation of crude oil contaminated land on agricultural resources in Umuechem in Etche Local Government Area of Rivers State, Nigeria. Purposive sampling technique and a survey research design was adopted with the use of structured questionnaires administered on a sample size of sixty two (62) persons whose farmlands and other agricultural resources were contaminated and thereafter remediated. The sample size was made up of fifty four (54) literate and eight (8) illiterate persons. The questionnaire was interpreted in native language to the illiterate persons by either their children or any other relative. The data obtained from the survey were analysed using descriptive statistics such as tables and statistical package for social sciences (SPSS).The findings obtained indicated that there was a post-remediation low-crop-yield and recommended that remediation consultants should adopt techniques capable of completely removing contaminants from the environment.